Dressed perturbation theory for the quark propagator: Fernando Enrique Serna Algarín. - - Algarín, F.E.S [UNESP] (2013)
The rainbow-ladder approximation is a simple nonperturbative truncation scheme for nonperturbative calculations in Quantum Chromodynamics (QCD). It provides satisfactory results for the ground-states of light pseudoscalar and vector mesons, but for excited and exotic states, as well as for heavy-light mesons, this truncation provides less accurate results. In the present dissertation we have proposed a novel approach to go beyond the rainbow-ladder truncation, which we name dressed perturbation theory. The guiding principle of the approach is to modify the quadratic part of the QCD action by the addition of self-energy terms for the quarks and gluons, and perform perturbative calculations with the interaction action subtracted by the same self-energies. Instead of noninteracting propagators of traditional perturbative QCD calculations, the novel perturbative scheme is performed with dressed propagators. The self-energies used in the dressed propagators can be taken from the ladder approximation, or from lattice QCD simulations. Our main concern in the dissertation is the application of the formalism to the the quark propagator. The lowest nontrivial order corrections are two-loop vertex corrections. Numerical results are obtained for quark mass function and pion properties in the chiral limit for a simple ansatz for the gluon self-energy